Exploring The Relationship Between Lactate Dehydrogenase Levels, Leukocyte Counts, Low Birth Weight, and The Severity of Preeclampsia in Pregnant Women: A Cross-Sectional Study at Saiful Anwar Hospital Malang (July 2021 to June 2022) - Bambang Rahardjo; Talita Nandia Primarintan (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: This study investigates the connection between lactate dehydrogenase (LDH) levels, leukocyte counts, low birth weight, and the severity of preeclampsia among pregnant women. Conducted at Saiful Anwar Hospital in Malang from July 2021 to June 2022. Material and Methods: This research utilizes a descriptive and analytical observational approach with a cross-sectional design. Pregnant women meeting specific criteria were evaluated for LDH levels, leukocyte counts, preeclampsia severity, and newborn birth weights. Statistical analyses, including the Kruskal-Wallis test and Spearman correlation, were employed to explore relationships and significance among variables. Results: There is significant differences in LDH levels and low birth weight across patients with mild preeclampsia, severe preeclampsia, and eclampsia. LDH levels were linked to preeclampsia severity, while low birth weight correlated with eclampsia. Leukocyte levels, however, did not exhibit notable differences among these group. Conclusion: This study underscores the necessity of early assessment and monitoring of these factors in pregnant women, aiming to enhance maternal and fetal outcomes. Further research is recommended to validate these findings in diverse populations and explore additional risk factors associated with preeclampsia-related conditions. In conclusion, this research illuminates the interplay between LDH levels, leukocyte counts, low birth weight, and preeclampsia severity. The outcomes emphasize their importance as potential markers for evaluating and managing preeclampsia-related complications.